Procedure for the implementation of a virtual CNC lathe - Anitelle, Anésio Tarcisio (2001)
The paper presents a work executed in the virtual prototyping area. It is described as a procedure for the implementation of a CNC (Computerized Numeric Command) lathe prototype using software for virtual environment development. This procedures focus mainly on the interlocking system (functionality) and geometric model (physical design) of the lathe. Consequently, this work aims at checking the potential and limitations of this graphic interface tool, considering the complexity of the data required for product prototyping in manufacturing or assembly.